Pemanfaatan Teknologi Berbasis Mobile Untuk Manajemen Kontrol Nilai Dan Absensi Siswa Pada Mts Al-Ittihadiyah Medan - Saut Parsaoran Tamba; Didik Rifaldi Hia; Donny Prayitna; Andina Riandra Tryvaldy (Jurnal Sains dan Teknologi, 2020)
Madrasah Tsanawiyah (MTs) Al-Ittihadiyah is an educational institution that is equivalent to a Junior High School (SMP)located in the city of Medan, where the current value system and student attendance are not computerized and even mobile. Such studentvalue and attendance systems have weaknesses, among others, a lack of a security system and can cause errors in data processing. For thisreason, in this study a mobile-based student attendance and score application was created to answer the problems faced so far. To achievegood learning achievement, it can be seen from the value and attendance that a student produces from the results of the learning processhe has lived. From the learning process, tests or tests are then carried out and the results will be processed to produce a value, both forcognitive values and affective values. Given the importance of student grades and attendance data, these data need to be managedproperly. For that we need a good information system so that student grades and attendance data are more organized. The system to bebuilt is a mobile technology for student attendance and value control management. With this system, it will be much better than themanual system.